Methodological Challenges faced by Foreign Language Teachers in addressing Students’ Language Learning Difficulties - Lara Portillo, Verónica Elizabet; Ramírez Martínez, Roberto Arnoldo (Papanda Publisher, 2025)
This study, conducted through a descriptive case study at Universidad Don Bosco (UDB[1]), examined the methodological challenges faced by English and French teachers when supporting students with language learning difficulties. Twenty instructors participated between May and June 2025 using a Likert-scale questionnaire and open-ended questions. Findings reveal a highly adaptive teaching response: 95% reported systematic use of multisensory strategies (visual, auditory, kinesthetic); 90% stated that feedback to these students requires more time and care; 65% modified assessment procedures; and 85% reported greater flexibility in classroom time management. Additionally, 95% reinforced grammatical content frequently, and 65% designed differentiated activities, while half sought further training. Thematic analysis identified four recurring dimensions: pedagogical differentiation, progressive scaffolding, collaborative learning, and technological support. Nonetheless, tensions persist between inclusive teaching aspirations and classroom realities marked by time constraints, uneven learning pace, and inconsistent evaluation practices. The study concludes that inclusive language instruction cannot depend solely on individual teacher initiatives but requires institutional guidelines, adaptable materials, protected pedagogical time, and professional development focused on formative assessment and second-language production. Limitations include the single-site context, self-reported data, and a non-experimental design. [1] UDB refers to Universidad Don Bosco, a higher education institution located in Soyapango, El Salvador.